A rule–based service framework for supply chain management. (29th December 2014) - Moynihan, Paul; Dai, Wei
In this paper, we introduce a service framework for supply chain management, which runs on a heterogeneous network and leverages the power of an inference engine to manage networks and supply chain entities. Details of design and implementation of the framework are given along with the discussions on the preliminary experimental results and impacts for industries. Future work points to further investigation of heterogeneous services and their interactions within the framework.